To correctly order the steps used to solve the equation \(4(3x - 2) = -24\), we will arrange them as follows:
-
Distribute 4 on both sides of the equation. \[ 4 \cdot 3x - 4 \cdot 2 = 4 \cdot -24 \] which simplifies to: \[ 12x - 8 = -96 \]
-
Add 8 to both sides of the equation. \[ 12x - 8 + 8 = -96 + 8 \] which simplifies to: \[ 12x = -88 \]
-
Divide both sides of the equation by 12. \[ \frac{12x}{12} = \frac{-88}{12} \] which simplifies to: \[ x = -\frac{88}{12} \text{ or } x = -\frac{22}{3} \]
Thus, the order of the steps is:
Step 1: Distribute 4 on both sides of the equation.
Step 2: Add 8 to both sides of the equation.
Step 3: Divide both sides of the equation by 12.